Le nationalisme québécois, bougie d’allumage d’un nouveau Canada - Sylvie Lacombe (Communication)
The author analyzes 29 editorials published by the Toronto daily newspaper The Globe and Mail during the 1980 referendum campaign in the province of Quebec. She found that the comments made regarding Quebec nationalism reveal in part the Anglo-Canadian sense of national identity. Political scientists usually associate the political restructuring of the Canadian state with the 1982 patriation of the constitution. This restructuring was already discernible in 1980 with the assertion of the principle of equality among Canadian provinces and the revised vision of the Canadian Federal State as a unitary National State.